Study of Clinical Profiles, Risk Factors and Coronary Angiographic Patterns in Female Patients Presenting with Anginal Chest Pain in a Tertiary Care Centre of Nepal - Adhikari, Suman; Gajurel, Ratna Mani; Poudel, Chandra Mani; Shrestha, Hemant; Thapa, Sanjeev; Devkota, Surya; Manandhar, Bhawani; Khanal, Rajaram; Shakya, Smriti; Yadav, Vijay; Sharma, Manju; Sahi, Ravi; et al. (Nepalese Heart Journal, 2022)
Background and Aims: Coronary artery disease is one of the important causes of deaths in females in many countries. Females with chest pain are more likely to be treated in a different way as compared to males at the time of presentation. Worldwide, there has been a considerable rise in the number of females who are undergoing coronary angiography recently.Methods: This study was a single-centre, prospective, observational study conducted in the department of cardiology, MCVTC, Tribhuvan University, Nepal. The study period was from 5th  July 2020 to  4th July 2021.155 female patients with anginal chest pain were enrolled. Data were collected after thorough history taking, physical examination, laboratory investigations, and coronary angiography. They were further divided into three age groups:65 years. Subsequently statistical analysis was done using latest version of SPSS.Results: The mean age of the patients was 59.64 years (SD=11.428). There were 119 (76.77%) postmenopausal patients. The most prevalent risk factor of IHD  was HTN (43.87% ). Obesity/overweight was most common (58.62%) in those with age